Demokracja lokalna a idea ograniczenia liczby kadencji wójtów(burmistrzów, prezydentów miast) - Kowalik, Janina (Political Preferences, 2015)
Local democracy and the idea of term limits voits (mayors) For some time there is a debate on the term of office mayor sand presidents of cities. Subject of the article is to analyze views on democracy and indicators of democracy, including the local dimension in the context of the controversy over the long cadence reeves impact on the functioning of local government. The author also extends to public opinion polls on the issue of limiting the cadence of mayors. We are analyzing the arguments of supporters and opponents of limiting the cadence of executive power in municipalities, as well as the dilemmas associated with the consequences of such restrictions for the quality of democracy. Limiting cadence has as many supporters as opponents - both sides have serious arguments for their positions. Key words: democracy, local democracy, local elections, cadences mayors and presidents of cities